Towards long-term intracranial pressure monitoring based on implantable wireless microsystems and wireless sensor networks - Fernandes, J. (2015)
Ambient Assisted Living (AAL) aims to provide support to healthcare professionals making use of sensing, and information and communication technologies. Brain related information is becoming more and more relevant for many pathologies, but access to long-term information from brain to feed such AAL technologies is still giving the first steps. One main issue when recording signal from the brain is the available room for sensing device placement. Since available room is limited, battery-less solutions are welcome. Also, AAL solutions to be developed should consider not only the sensing device, but also the entire supporting framework. This paper introduces a solution for long-term monitoring of intracranial pressure using a wireless microdevice and a wireless sensor network. This work introduces a solution to achieve an enough miniaturized pressure sensor, powered by a wireless link, and analyzes the suitability of a wireless sensor network to support the data dissemination.